1983
DOI: 10.1163/156853983x00552
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Mechanisms of Social Organization in Monkeys

Abstract: Observations on a captive group of patas monkeys were supplemented with field observations to analyse the process by which a gregarious animal keeps track of the position and activity of other group members and regulates the distance between them and itself. This process can take place without the exchange of specialised signals (displays) and is described as a mechanism of group organisation alternative to a mechanism based on the exchange of displays. Displays and formalised interaction patterns can provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(25 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…Therefore, remaining close and behaviorally neutral (not affiliative and not agonistic) may be sufficient to clearly indicate the cessation of a conflict and the conflict participants' intent to not engage in further conflict at the present time (DE WAAL & YOSHIHARA, 1983). ROWELL and OLSON (1983) suggested that a change in spatial position communicated a change in social relationship. Close proximity may allow a conflict partner to monitor their opponents' movements and adjust their position accordingly.…”
Section: Proximitymentioning
confidence: 99%
“…Therefore, remaining close and behaviorally neutral (not affiliative and not agonistic) may be sufficient to clearly indicate the cessation of a conflict and the conflict participants' intent to not engage in further conflict at the present time (DE WAAL & YOSHIHARA, 1983). ROWELL and OLSON (1983) suggested that a change in spatial position communicated a change in social relationship. Close proximity may allow a conflict partner to monitor their opponents' movements and adjust their position accordingly.…”
Section: Proximitymentioning
confidence: 99%
“…Unlike savannah-dwelling primates, forest guenons are often out of sight from each other. Social interactions are much less common because they spend more effort monitoring each other's behaviour and adjusting their own spatial position accordingly (Rowell and Olson 1983;Rowell 1988). Instead, guenons typically emit social calls to overcome the constraints of poor visibility in the forest and maintain group cohesion (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…and social interchange. As a consequence, status is communicated with a combination of social gestures, postures and vocalizations in addition to attending visually to others (see Rowell and Olson, 1983;Johnson and Karin-D'Arcy, 2006). In A. burtoni, however, relatedness and age do not appear to play a role in the status hierarchy, which is quite fluid and depends on the ongoing aggressive encounters.…”
Section: Dominant Malementioning
confidence: 99%